ANALISIS STRATEGI PENGEMBANGAN USAHA KOPI ARABIKA PADA USAHA MENTUANGIN COFFEE KABUPATEN ENREKANG - Muh Nicvan; Burnama Azhari; Rista Astari Rusdin; Wilda Widiawati; Zainal Potton; Baharuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to analyze the internal and external factors affecting the business development of Arabica coffee at Mentuangin Coffee, Enrekang Regency, and to formulate appropriate business development strategies. The research employed a descriptive qualitative approach using SWOT analysis. Data were collected through observations, interviews, and documentation. The data were analyzed using the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), SWOT Matrix, and Internal-External (IE) Matrix. Recommended strategies include increasing production capacity, developing innovative Arabica coffee products, expanding market reach through digital marketing and strategic partnerships, improving the quality of human resources, and strengthening collaboration with local coffee farmers and business partners to enhance competitiveness and ensure long-term business sustainability